Water Availability, Soil Characteristics, and Confounding Effects on the Patterns of Biocrust Diversity in the Desert Regions of Northern China - Sun, Jingyao; Li, Xinrong (Frontiers in Plant Science, 2022)
The species diversity of biocrusts is an important community characteristic in determining their multiple ecosystem functions. Hence, understanding the diversity patterns of biocrusts and their environmental drivers is of fundamental importance. However, explain variables often correlated with each other; thus, the confounding effects among them may arise and result in spurious causal relationships and biased ecological inferences. In this study, we investigated the richness of three biocrust-forming components (mosses, lichens, and cyanobacteria–algae) and their environmental variables across six desert regions of northern China. A comparison between conventional redundancy analysis (RDA) and structural equation model (SEM) was conducted to study the environmental driver-richness relationship and the confounding effects. Our results showed that three latent variables related to water availability, soil texture, and soil salinity and sodicity, could account for the main environmental variations and explain the diversity patterns of biocrusts at the intracontinental scale. Water availability was positively and negatively related to the richness of mosses and cyanobacteria–algae, respectively, while soil texture was positively related to the richness of lichens. In addition, environmental variables confounded with each other caused distinct driver-richness relationships between results of RDA and SEM. Therefore, we suggest that future multivariable studies should utilize path analysis in conjunction with conventional canonical ordination to facilitate more rigorous ecological inferences.